Reproductive Science for High School Students: A Shared Curriculum Model to Enhance Student Success. Issue 1 (1st July 2016) - Castle, Megan; Cleveland, Charlotte; Gordon, Diana; Jones, Lynda; Zelinski, Mary; Winter, Patricia; Chang, Jeffrey; Senegar-Mitchell, Ericka; Coutifaris, Christos; Shuda, Jamie; Mainigi, Monica; Bartolomei, Marisa; et al.
Abstract: The lack of a national reproductive biology curriculum leads to critical knowledge gaps in today's high school students' comprehensive understanding of human biology. The Oncofertility Consortium developed curricula that address the basic and clinical aspects of reproductive biology. Launching this academy and creating easy-to-disseminate learning modules allowed other universities to implement similar programs across the country. The expansion of this informal, extracurricular academy on reproductive health from Northwestern University to the University of California, San Diego, Oregon Health & Science University, and the University of Pennsylvania magnifies the scope of scientific learning to students who might not otherwise be exposed to this important information. To assess the experience gained from this curriculum, we polled alumni from the four centers. Data were collected anonymously from de-identified users who elected to self-report on their experiences in their respective reproductive science academy. The alumni survey asked participants to report on their current academic standing, past experiences in the academy, and future academic and career goals. The results of this national survey suggest the national oncofertility academies had a lasting impact on participants and may have contributed to student persistence in scientific learning.